NEUTROPHIL TO LYMPHOCYTE RATIO VS PLATELETS TO LYMPHOCYTE RATIO: BIOMARKERS TO PREDICT SEVERITY OF DISEASE AND THEIR COMPARISON IN PATIENTS OF COVID-19 - Adil, Muhammad; Baig, Zahid Farooq; Amir, Muhammad; Chatha, Sohail Saqib; Habib, Aamir; Majid, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine and compare Neutrophil to Lymphocyte Ratio (NLR) and Platelet to Lymphocyte Ratio (PLR) in predicting severity of disease in patients with COVID-19. Study design: Descriptive comparative study. Place and Duration of study: Department of Medicine, CMH Thal from April to July, 2020 Patients & Methods: 61 patients of COVID-19 confirmed through polymerase chain reaction were recruited and divided into severe and non severe disease. Complete blood counts were done. Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio were calculated and analyzed. Results: 14 patients (23%) of severe disease had mean age of 49.93±19.42 and 47 patients (77%) with non-severe disease had mean age of 33.32±9.16. The mean Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte ratio in patients who had severe disease was 7.20±4.20 and 204.25±148.42 (p=0.001 and p=0.026) respectively. The diagnostic performance of both Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio produced statistically significant area under the curve (AUC), (p <0.001). The adjusted and unadjusted area under curve for Neutrophil to Lymphocyte Ratio was 0.92 (95% CI: 0.85–1.00) and 0.923 (95% CI: 0.839-1.000) and for Platelet to Lymphocyte Ratio it was 0.883 (95% CI: 0.781–0.985) and 0.825(95% CI: 0.707-0.943) respectively. Conclusion: Elevated Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio are independent biomarkers which predict severity of disease in COVID-19 patients with Neutrophil to Lymphocyte Ratio being better predictor in terms of diagnostic accuracy. Keywords: Corona virus disease 2019 (COVID‐19), Neutrophil to Lymphocyte ratio, Platelet to Lymphocyte ratio